EUROPEAN EXPERIENCE OF FINANCIAL MARKETS REGULATION AND OPPORTUNITIES FOR ITS APPLICATION IN RUSSIA - R. A. Kasyanov (Vestnik MGIMO-Universiteta)
Large-scale improvement is in store for the European financial regulators. Reforms are being carried out at the supranational level of the European Union whereas the national legislation of the EU member-states is being refined. Similarly, the system of financial regulation in the Russian Federation is about to change prompting creation of a mega-regulator for the financial market on the basis of the RF Central Bank to be launched in August of 2013 with the regulation and supervision shared by the RF Ministry of Finance and Central Bank respectively. As a result, the current regulator, Federal Financial Markets Service, will be abolished with its staff to be employed by the Central Bank. Whether the initiative will be successful depends on a number of factors, among them appropriate application of existing regulation models taking into account the following aspects: participation/non-participation of the market and professional community in the regulation; the subject and the field of regulation. Scrutiny of the European regulators active at the level of the European Union, as well as the national experience of the financial regulators of Luxemburg and Belgium gives a better insight into the prospects of the regulatory reform that is supposed to make the future system intelligible, lucid and self-sufficient, which should be reflected in the underlying legislation.